Maternal Knowledge and Practices for Prevention of Acute Diarrheal Diseases in Children under 5 years of age - Manzoor, Iram; Mumtaz Joya, Aneeqa; Qureshi, Irum; Muhammad Yousaf, Muhammad Faizan; Bin Shahid, Muhammad Fasseh; Mubariz, Muhammad; Maqbool , Saadia (Journal of University College of Medicine and Dentistry, 2022)
Background: Diarrhea is the second major cause of mortality in children worldwide. Timely interventions by caregivers who are mainly mothers, can contribute towards a favorable prognosis of this condition in children. Aim: The purpose of conducting this study was to assess maternal knowledge and the practices regarding prevention of diarrheal diseases in children under the age of 5 years. Setting: This study was carried out in three hospitals at Lahore, Pakistan. Methods: An analytical cross-sectional study was conducted from January to July 2020 and a convenience sampling technique was used for data collection. Data was collected from 158 mothers of children under 5 years of age by using a self-structured, pre-tested questionnaire. Chi square test was applied and p-value <0.05 was taken as significant. Results: A total of 158 mothers responded to the study questionnaire; mean age of the participants was 28.4+ 7.6 years, 22.8% were illiterate, 84.2% were housewives, and 37.4% had income more than 31000 rupees/month. The majority (43.1%) had ‘poor’ knowledge, 24% had’ poor’ attitudes and practices while 12% had better practices. Significant associations were observed between mother’s knowledge with education (p-value=0.004), income (p-value=0.001), frequency of diarrhea in a child (p-value=0.053) and practices with education (p-value =0.039). Conclusion: This study showed the direct relationship between mother’s literacy level and family income with better knowledge and feeding practices of children regarding prevention of diarrhea. It has highlighted the role of mothers in the management of acute diarrheal diseases.